Effect of Renal and Left Ventricular Function on Serial Pulmonary Arterial Pressure Changes after Device Closure of Atrial Septal Defect. (18th January 2021) - Shin, Chul; Yoon, Young Won; Kim, In-Soo; Kim, Jong-Youn; Min, Pil-Ki; Lee, Byoung Kwon; Hong, Bum-Kee; Rim, Se-Joong; Kwon, Hyuck Moon; Choi, Eui-Young
Abstract : Background . The age of candidates for device closure of atrial septal defect (ASD) has been increasing. Thus, concerns exist about dyspnea aggravation or atrial fibrillation development after device closure due to augmentation of left ventricular (LV) and left atrial (LA) preload. This study aimed to examine patterns and determinants of serial pulmonary arterial pressure and left ventricular filling pressure changes after device closure of ASD. Methods . Among the 86 consecutive patients who underwent percutaneous device closure of ASD, those with end-stage renal disease or those without pre- or postprocedural Doppler data were excluded. The clinical, transesophageal, and transthoracic echocardiographic findings of 78 patients were collected at baseline, one-day postprocedure, and one-year follow-up. Results . The mean age of study patients was 49.8 ± 15.0 years, and the average maximal defect diameter and device size were 20.2 ± 6.0 mm and 23.8 ± 6.4 mm. Four patients (5.6%) underwent new-onset atrial fibrillation, and five patients (6.4%) took diuretics within one-year after closure. Some patients ( n = 21; 27%) exhibited paradoxically increased tricuspid regurgitant velocity (TRV) one-day postprocedure; they also were older with lower e', glomerular filtration rate, and LV ejection fraction and a higher LA volume index. However, even in these patients, TRV deceased below baseline levels one-year later. Both E/e' and LA volume index significantly increased immediately after device closure, but all decreased one-year later. Larger defect size and higher TRV were significantly correlated with immediate E/e' elevation. Conclusion . In older, renal, diastolic, and systolic dysfunctional patients with larger LA and scheduled for larger device implantation, peri-interventional preload reduction therapy would be beneficial.